2012
DOI: 10.1016/j.bmc.2012.09.022
|View full text |Cite
|
Sign up to set email alerts
|

4-Isoxazolyl-1,4-dihydropyridines exhibit binding at the multidrug-resistance transporter

Abstract: The 4-Isoxazolyl-dihydropyridines (IDHPs) exhibit inhibition of the multidrug-resistance transporter (MDR-1), and exhibit an SAR distinct from their activity at voltage gated calcium channels (VGCC). Among the four most active IDHPs, three were branched at C-5 of the isoxazole, including the most active analog, 1k.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…5b,1416,24 The danzyl probes, most notably 3c , in addition to the expected set of signals for the isoxazolyl-DHP, also exhibited a second set of signals with pronounced magnetic anisotropy in typical organic solvents (i.e., CDCl 3 ), and of equal intensity. Nuclear Overhauser spectroscopy evidenced interactions between the DHP C(2) and C(6) methyls with the Isoxazolyl C(3) phenyl, and the Isoxazolyl C(3) phenyl with the dimethyl amino groups of the dansyl moiety, indicative of a folded conformation.…”
Section: Conformational Dynamics Of the Fluorescent Probesmentioning
confidence: 94%
See 2 more Smart Citations
“…5b,1416,24 The danzyl probes, most notably 3c , in addition to the expected set of signals for the isoxazolyl-DHP, also exhibited a second set of signals with pronounced magnetic anisotropy in typical organic solvents (i.e., CDCl 3 ), and of equal intensity. Nuclear Overhauser spectroscopy evidenced interactions between the DHP C(2) and C(6) methyls with the Isoxazolyl C(3) phenyl, and the Isoxazolyl C(3) phenyl with the dimethyl amino groups of the dansyl moiety, indicative of a folded conformation.…”
Section: Conformational Dynamics Of the Fluorescent Probesmentioning
confidence: 94%
“…21,22 This represents a significant increase in MDR-1 binding compared to IDHP- 1 , which exhibited a value of 48.9% in the PDSP assay. 23,24 …”
Section: Multidrug-resistance Inhibition (Mdr-1)mentioning
confidence: 99%
See 1 more Smart Citation
“…In our initial study, we found that branching at the C(5) of the isoxazole gave rise to three of the four most efficacious IDHPs at MDR-1. 11 In a follow-up study, attachment of a fluorophore also enhanced activity. This suggested additional binding opportunities in proximity to the putative nucleotide binding domain (NBD) of IDHPs ( vide infra ).…”
mentioning
confidence: 99%
“…Dihydropyridines (DHPs) have been under intense study for many years for their ability to inhibit the multidrug transporter. 9,10 More recently we have reported that 4-isoxazolyl-1,4-dihydropyridines (IDHPs) have significant binding at this target, 1113 and a unique structure activity relationship (SAR) which diverges from their voltage gated calcium channel (VGCC) activity. In our initial study, we found that branching at the C(5) of the isoxazole gave rise to three of the four most efficacious IDHPs at MDR-1.…”
mentioning
confidence: 99%